Experimental Study of Performance and Emissions of a 4-Stroke Engine with a Capacity of 110cc - Muhammad, Rouf; Pramanda, Wibi; Widyantoro, Arif; Joko Sumbogo, Yuliarto; Jiwo Satrio, Hutomo; Safi'i, Muhamad; Ramadhan Nur, Hamid; Ibrahim Soumi, Andi (Politeknik Caltex Riau, 2025)
In addition to adding ferrite beads to the ignition coil, this study attempts to examine the effects of different spark plugs and ignition coils. Ferrite beads are employed to mitigate electrical noise and enhance electrical efficiency. This research facilitates the examination of engine performance and exhaust emissions, thereby offering insight into the combustion process within the combustion chamber. This study used a 4-stroke Otto engine with a displacement of 110 cc, powered by RON 92 gasoline. We utilize three types of spark plugs: Denso U22FS-U, NGK 14 mm, and Iridium IU27. Two varieties of ignition coils are employed: PCX 150 and COL9001, supplemented by ferrite beads. Dynotes are utilized to assess engine performance, while gas analyzers are employed to evaluate exhaust pollutants. The criteria examined for engine performance include torque and power, while exhaust emission parameters consist of CO, CO2, O2, and HC. The findings indicate that the NGK 14-mm spark plug, when paired with a COL9001 ignition coil and supplemented with a ferrite bead, achieves a peak torque of 7.67 Nm at 6514.42 rpm and a maximum power output of 5.73 kW at 72813.93 rpm. This setup yields minimal emissions and favorable fuel consumption when it is implemented. This study's findings offer significant insights and references for tactics including spark plugs, ignition coils, and ferrite beads.